Efektifitas Ekstrak Etanol Kelopak Buah Sonneratia alba sebagai Larvasida Aedes aegypti - Ratna Yuliawati; Deny Kurniawan; Indah Permata Sari (Poltekkes Kemenkes Yogyakarta, 2020)
Sonneratia alba is a type of mangrove in Indonesia. Various studies of phytochemicals on Son-neratia alba suggests that this herb is very potential as anti-fungal and larvasida, especially in the skin of the stem. However, it is still a few study on the utilization of shell fruit Sonneratia alba. Therefore, it is necessary to conduct phytochemicals study on S. alba fruit petals that can be useful as a larvasida. The process of this research is in the form of extraction of Sonneratia alba fruit shell by using meceration ethanol method. The maceration results are then tested in order to know the content of phytochemical active compounds of S. Alba furit shell, and then were tested as larvacide to Aedes aegypti instar II/IV with concentration of 500, 1000, 2000, 3000, and 4000 ppm. Based on the results of the maceration, fruit petals extracts of S. alba on solvents of ethanol amounted to 7,74%. The results of the phytochemicals shos that the ethanol solvent contained flavonoid compounds and carbohydrates. The test results as larvacide show that the extract of ethanol petals fruit S. alba at concentrations of 500 ppm has average larva death as much as 23,3%, 1000 ppm concentration has 26,7%, 2000 ppm concentration has 37,7%, 3000 ppm concentration has 50% and 4000 ppm concentration has 63,3%. Thus, ethanol extract fruit shell of Sonneratia alba are effective in killing Aedes aegypti larvae in the concentration of 3000 and 4000 ppm.